The mediating role of trust in the relationship between authentic leadership, integrity, and organizational commitment - Christine Masada Hirashita Tobing; Sri Setyaningsih; Dian Wulandari (Jurnal Konseling dan Pendidikan, 2026)
This study aims to analyze the Influence of authentic leadership and integrity on teachers’ organizational commitment, both directly and indirectly through trust as a mediating variable. This study was conducted among 135 private high school teachers in Depok City, selected using multistage random sampling. Data were collected through a questionnaire with a Likert scale and analyzed using path analysis in SPSS 25.0. The results showed that all variables had a positive and significant Influence. Specifically, authentic leadership had a direct Influence on organizational commitment (β_y1 = 0,258) and on trust (β_31 = 0,223). Integrity also had a direct iInfluenceon organizational commitment (β_y2 = 0,213) and on trust (β_32 = 0,274). Furthermore, trust has been shown to mediate the relationship between authentic leadership and integrity and teachers’ organizational commitment. These findings confirm that increasing teacher loyalty and emotional attachment can be achieved sustainably through developing honest leadership, strengthening moral values, and building a work climate based on mutual trust.